Beyond the pill: advocating internet-based cognitive behavioral therapy for insomnia in Pakistan - Shakoor, Ammen; Shakoor, Aiyaan (Journal of the Pakistan Medical Association, 2026)
I would like to highlight internet-based cognitive behavioral therapy for insomnia (CBT-I) as a promising, evidence-based, yet underutilized treatment option in Pakistan. While benzodiazepines and other sedative-hypnotics remain the default approach in many clinical settings, non-pharmacological interventions such as sleep hygiene practices and CBT-I are often overlooked, despite being internationally recognized as first-line treatment modalities, as recommended by the National Institute for Health and Care Excellence (NICE) guidelines.1 A recent randomized controlled trial from Hong Kong investigated the effectiveness of internet-based self-help CBT-I among adults in a community setting and reported strong, clinically meaningful findings in favor of its use.2 Participants demonstrated statistically significant improvements in sleep quality, with marked reductions in insomnia symptoms, pre-sleep arousal, maladaptive sleep hygiene behaviors, and dysfunctional sleep-related beliefs. The intervention also resulted in measurable improvements in daytime functioning, including reduced depression, anxiety, and cognitive impairments, alongside enhanced overall quality of life. Notably, the study identified pre-sleep arousal as the strongest mediator of insomnia outcomes, offering valuable insight into potential targets for early intervention. Despite these encouraging findings, the management of insomnia in Pakistan remains largely pharmacological. Benzodiazepines and other sedative-hypnotics are frequently prescribed as first-line agents, often without adequate evaluation or education on sleep hygiene practices. This over-reliance is concerning, given their well-documented side effects, potential for dependence, and limited long-term efficacy. A local study from medical outpatient clinics reported high and often inappropriate benzodiazepine use among patients.3 Another study conducted in Karachi revealed that these drugs were frequently dispensed without prescriptions by pharmacists.4 Non-pharmacological interventions such as cognitive behavioral therapy and sleep hygiene remain underutilized in routine care. Beyond the clinical concerns surrounding pharmacological overreliance, psychosocial factors also limit the uptake of behavioral interventions in Pakistan. Mental health stigma remains a significant barrier to in-person therapy, often deterring individuals from seeking help. In this context, internet-based CBT-I holds unique potential: its independent nature preserves patient anonymity and autonomy, mitigating stigma-related hesitations. Moreover, the growing accessibility of technology, with over 116 million internet users reported in early 2025, up from 82.9 million in 20225, further amplifies the potential reach of this personalised intervention. To ensure effective implementation, collaborationbetween clinicians and psychologists is essential to educate patients about internet-based CBT-I and facilitate its adoption. Given its accessibility, evidence-based efficacy, and potential to overcome long-standing treatment barriers, it is imperative that greater awareness is raised regarding this valuable therapeutic modality.